2020
DOI: 10.1002/cjoc.202000491
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Tandem Carbonylative Aza‐Wacker‐Type Cyclization of Nucleophile Tethered Alkene to Access Fused N‐Heterocycles

Abstract: Main observation and conclusion Although tandem reactions offer rapid access to structurally complex molecules in one‐pot reaction, the selectivity issue needs to be addressed particularly when incompatible step reactions are involved. Herein, we report the selective synthesis of fused N‐heterocycles from nucleophile‐tethered alkenylamide and carbon monoxide via palladium (Pd)‐catalyzed tandem carbonylative aza‐Wacker‐type cyclization. The electron‐deficient nature of amide N—H and the intramolecular coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The different reactive activity for the two substrates was rationalized by density functional theory (DFT) calculations, [ 12 ] and the distribution of Mulliken atomic charge [ 13 ] on carbon 8 of 5l (−0.657) showed higher electronic density than that on the corresponding carbon of 3h (−0.488) (Figure 2), which is favored for electrophilic cyclization process to form hydroxyl intermediate ( D in Scheme 2). By analogy with the previously reported mechanism [ 10b,11a ] and our expermental observation, a tentative mechanism was proposed with compound 5l : First, in the presenc of Mo(CO) 6 and phenanthroline, Pd(OAc) 2 converts to palladium CO complex A . Afterward, complex A reacts with the nitro‐ biarene 5l through single‐electron transfer and affords radical anion B .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The different reactive activity for the two substrates was rationalized by density functional theory (DFT) calculations, [ 12 ] and the distribution of Mulliken atomic charge [ 13 ] on carbon 8 of 5l (−0.657) showed higher electronic density than that on the corresponding carbon of 3h (−0.488) (Figure 2), which is favored for electrophilic cyclization process to form hydroxyl intermediate ( D in Scheme 2). By analogy with the previously reported mechanism [ 10b,11a ] and our expermental observation, a tentative mechanism was proposed with compound 5l : First, in the presenc of Mo(CO) 6 and phenanthroline, Pd(OAc) 2 converts to palladium CO complex A . Afterward, complex A reacts with the nitro‐ biarene 5l through single‐electron transfer and affords radical anion B .…”
Section: Resultssupporting
confidence: 81%
“…[ 9 ] Carbon monoxide is the most frequently employed reductant due to good selectivity and atomic economy. [ 10 ] Recently, CO‐surrogates were developed to overcome the limitation of hazardous pressurized gas manipulation, [ 11 ] but most cases focus on the construction of 5‐membered ring containing heterocycles. As part of our efforts to develop N ‐heterocycle synthesis, we have demonstrated that palladium‐catalyzed reductive cyclization with Mo(CO) 6 can be successfully applied in nitroalkene system to afford indole alkaloids.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 3 ] When the same palladium catalyst is capable to promote heterocyclization coupled with carbonylation, [ 4 ] formation of two new rings with incorporation of CO as a carbonyl function in a single synthetic operation may take place, with direct formation of carbonylated fused heterocycles. [ 1p‐q,5‐6 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…The palladium‐catalyzed aminative difunctionalization of alkenes to incorporate an amine group as well as another functional group has been employed as a robust methodology to construct highly functionalized alkylamines of high value in medicinal and material chemistry with benign efficiency in synthetic routine. [ 1‐7 ] When halogen is introduced in a position vicinal to a sulfonamide group, this halosulfonamidation not only results in improvements in biological applications of sulfonamide scafford, [ 8‐10 ] but also provides the platform for further transformations into various amine derivatives, e.g ., aziridines and diamines. [ 11‐18 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%